Pengaruh Self Assessment , Sosialisasi Perpajakan Dan Sistem Informasi Perpajakan Terhadap Tingkat Kepatuhan Wajib Pajak - Elia Rossa; Achmad Zauhar Muqtafi; Afifah Rohmawati; Alisya Athalia; Alya Syafikah Rani; Anissa Pujiwaty; Yuyun Yuyun (Jurnal Manajemen Riset Inovasi, 2024)
This article discusses the impact of self-assessment, tax socialization, and tax information systems on the compliance level of taxpayers using a qualitative method and literature review from various sources. Its aim is to evaluate the influence of three main factors: self-assessment emphasizing direct responsibility on taxpayers, efforts in tax socialization to enhance public awareness, and the impact of tax information systems on the ease of taxation processes. The findings indicate a beneficial and significant impact of these three factors on the compliance level of taxpayers.